Extraction and chemical analysis of lemongrass (cymbopogan citratus) exxential oil - Yahya, Liyana; Mirghani, Mohamed Elwathig Saeed; Jamal, Parveen (Research Journal of Chemistry and Environment, 2010)
Lemongrass is widely used in food technology as well as in traditional medicine. Thus, research should be done on this plant. However, nowadays most of the researches just focus on the lemongrass leaves. This project is focused on the extraction, identification and analyzation of bioactive compounds from lemongrass essential oil. The first part of the research work is to extract and optimize the potential yield of essential oil using steam distillation from various parts of lemongrass plant which are stems and leaves for doing comparison studies on essential oil. Optimization process is been done by using Design-Expert Software by applying parameters such as temperature and extraction time. The process considered extraction yield of essential oil (mass of essential oil per mass of raw material) as responses (leaves and stems separately) of the optimization process. The temperature and extraction time were found to have significant effect on the extraction yield. The stem part produced more oil compared to the leaves part. The bioactive components of essential oil from leaves and stems are then been compared by gas chromatography-mass spectrophotometer (GC-MS). The analysis on chemical composition on both parts showed the existence of bioactive components in both essential oils. This project is aim to identifying, quantifying and formulating potential bioactive compound from lemongrass essential oil for future commercialization.